Liquidity Preference and Stock Market Speculation - Krainer, Robert E. (Journal of Financial and Quantitative Analysis, 1969)
J. M. Keynes' theory of portfolio management (modified and refined by Tobin)occupied an important role in his analysis of the demand for money. According to this theory, financial investors were thought to vary the composition of their portfolios between money and securities on the basis of expected yields on securities. When yields were expected to rise, investors would shift out of securities and into money. Conversely, when yields were expected to fall, investors would shift out of money and into securities. Hence, the asset, or portfolio, demand for money was argued to be negatively related to the expected yields on securities.